The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1039/c5cc09110a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent columnar hybrid materials containing polyionic inorganic nanoclusters

Abstract: The ternary polyionic inorganic compound Cs2Mo6Br14 and 18-crown-6 ethers bearing two o-terphenyl units have been combined to design phosphorescent columnar liquid crystalline hybrid materials. The obtained host-guest complexes are very stable even at high temperatures. Depending on their surrounding atmosphere, these hybrids switch reversibly from a high-to-low luminescence state and show a very stable emission intensity up to 140 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…Such columnar organization of hexanuclear clusters remains scarce and has only been observed up to now in ternary polyionic inorganic compound Cs 2 Mo 6 Br 14 and 18-crown-6 ethers bearing two o-terphenyl units. 62 In addition, the association of emissive clusters with conducting stacking stacks of TP should be of great interest for applications in optoelectronic.…”
Section: Thermal and Self-organizing Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such columnar organization of hexanuclear clusters remains scarce and has only been observed up to now in ternary polyionic inorganic compound Cs 2 Mo 6 Br 14 and 18-crown-6 ethers bearing two o-terphenyl units. 62 In addition, the association of emissive clusters with conducting stacking stacks of TP should be of great interest for applications in optoelectronic.…”
Section: Thermal and Self-organizing Propertiesmentioning
confidence: 99%
“…61 Recently, an original supramolecular strategy using discotic crown-ether able to complex the alkali counter cations of the anionic cluster units has been developed to design columnar liquid crystals. 62 Triphenylene (TP) derivatives are archetypical of discotic liquid crystals (DLCs). 59 The large π-conjugated system with high symmetry can easily be functionalized and the grafting of linear alkyl chains from C4 to C11 allows the facile emergence of columnar mesophases of hexagonal symmetry (Col h ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, with iodine, the substitution via solution chemistry of apical I a by OCOC n F 2n?1 groups leads to Cs 2 Mo 6 I i 8 ðOCOC n F 2nþ1 Þ a 6 (n = 1, 2, 3) series [20,21]. From the viewpoint of optical properties, the Mo 6 [22,23]. Last but not least, the whole series Cs 2 Mo 6 X i 8 X a 6 (X = Cl, Br and I) has been used as precursor for their integration in silica nanoparticles Cs 2 Mo 6 X i 8 X a 6 @SiO 2 [2,3,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The inset of Figure (a) shows the red emission of the doped‐PUcc sample taken under a 365 nm irradiation and gives another evidence of the homogeneous integration of nanoclusters in PUcc. Recently, we showed that the nanocluster anion emission behavior toward a temperature modulation could be used to sense the molecular nanostructuration changes within a liquid crystalline hybrid material . Here, we decided to investigate if such ability could also be observed within a polymer matrix.…”
Section: Resultsmentioning
confidence: 99%